Oscillation Criteria for Third-Order Emden–Fowler Differential Equations with Unbounded Neutral Coefficients - George E. Chatzarakis; Said R. Grace; Irena Jadlovská; Tongxing Li; Ercan Tunç (Complexity)
New sufficient conditions for the oscillation of all solutions to a class of third-order Emden–Fowler differential equations with unbounded neutral coefficients are established. The criteria obtained essentially improve related results in the literature. In particular, as opposed to known results, new criteria can distinguish solutions of third-order differential equations with different behaviors. Examples are also provided to illustrate the results.